Decision Support Systems Recipient Program Keluarga Harapan (PKH) In Durian Kec.Pantai Labu Kab. Deli Serdang with the Simple Additive Weighting (SAW) Method: Decision Support Systems Recipient Program Keluarga Harapan (PKH) In Durian Kec.Pantai Labu Kab. Deli Serdang with the Simple Additive Weighting (SAW) Method - Rosulastri Purba; Hengki Tamando Sihotang (Jurnal Mantik, 2019)
This research examines how to design an application and build a decision support system in order to facilitate the process of determining beneficiaries of Program Keluarga Harapan (PKH). By using the Simple Additive Weighting (SAW) method, PKH beneficiaries are more targeted. The SAW method certainly uses a more accurate assessment because it is based on a criterion value of a predetermined preference weight. This research produces a system that is able to display the recommendation of prospective beneficiaries in accordance with the ranking of the criteria that have been determined according to the needs of the system